2015
DOI: 10.4103/0970-9290.176915
|View full text |Cite
|
Sign up to set email alerts
|

The autologous platelet rich fibrin: A novel approach in osseous regeneration after cystic enucleation: A pilot study

Abstract: The use of PRF in management of cystic lesions seems to be a novel therapeutic approach promoting faster osseous regeneration within 6 months postoperatively however further study is required with larger sample size and with a control group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 2 publications
2
15
0
Order By: Relevance
“…The mean amount and percentage of newly formed bone volume was higher in the experimental (0.78 cm 3 ; 82.6%) than control group (0.62 cm 3 ; 68.38%). Bone density does not increase, but the difference was not statistically significant.…”
Section: Interventionsmentioning
confidence: 72%
See 1 more Smart Citation
“…The mean amount and percentage of newly formed bone volume was higher in the experimental (0.78 cm 3 ; 82.6%) than control group (0.62 cm 3 ; 68.38%). Bone density does not increase, but the difference was not statistically significant.…”
Section: Interventionsmentioning
confidence: 72%
“…Regenerative therapy in oro-dental and maxillo-facial defects is challenging because the oral cavity has several tissues with distinct cell populations (ectodermal and mesodermal), making regenerative procedures more complex [1]. Bone and soft tissue regeneration may be indicated for managing defects subsequent from several conditions, such as congenital defects (cleft lip and palate), alveolar bone resorption, periodontal defects (recession coverage and furcation defects), cystic cavities, bone infection (osteomyelitis), and traumatic bone destruction [1][2][3][4]. Nowadays, the current clinical approaches have several limitations, namely limited self-renewal capacity and/or limited donor supply, risk of immune response, operative time, and costs and donor site morbidity.…”
Section: Introductionmentioning
confidence: 99%
“…The results of the presented research indicate that the application of CGF material in oral surgery procedures such as teeth extractions reduces the intensity of post-operative alignments. Also Singh et al and Meshram et al concluded that PRF offers many advantages such as decrease of the frequency of intraoperative and postoperative bleeding, promotion of more rapid soft tissue healing and rapid vascularization of the healing tissue by delivering growth factors [7,11]. In conclusion, use of CGF in intraosseous bone defects can result in successful bone formation as it promotes faster regeneration because of gradual release of growth factors lodged in the fibrin matrix.…”
Section: Healing Process Pointsmentioning
confidence: 97%
“…[7] Bone regeneration after periapical surgery is influenced by four critical factors -primary wound closure, angiogenesis as a blood supply and source of undifferentiated mesenchymal cells, space maintenance and stability of wound (PASS Principle). [8] PRF helps to obtain fibrin membranes enriched with platelets and growth factors. PRF releases autologous growth factors gradually for atleast 1 week and upto 28 days.…”
Section: Discussionmentioning
confidence: 99%